Review of Comprehensive Measurements of Speciated NOy and its Chemistry: Need for Quantifying the Role of Heterogeneous Processes of HNO3 and HONO - Hajime Akimoto; Hiroshi Tanimoto (Aerosol and Air Quality Research)
Abstract To improve the credibility of chemistry schemes employed in chemical transport models (CTMs) aiming at predicting ozone mixing ratios in urban, rural, and regional scales, validation of models not only by observational data of O3 and NOx but also by individual species of reactive nitrogen NOy is necessary because the formation and dissipation of O3 in the atmosphere occur via reactions accompanying the transformation of NOx and NOy. The disagreement of the simulated results of CTM with observational data of HNO3 and HONO have often been reported, and this paper reviews previous studies on the heterogeneous “renoxification” reaction of gaseous HNO3 to form NO, NO2, and/or HONO; the formation of HONO from the heterogeneous dark reaction of NO2 and H2O, and the photolysis of adsorbed HNO3 and NO3 − on surfaces. For the further validation of CTMs with individual species of NOy, previous field studies of comprehensive observation of NOy speciation in ground-based and aircraft campaigns have also been reviewed. Studies combining observations of speciated NOy and model simulations need to be performed to improve chemistry models used in CTMs.